Induction of Alzheimer's disease-related tau pathology by heparan sulphates and its regulation via TGF-ß - Castillo-Negrete, Rafael; Justus Liebig University Giessen (My University, 2023)
Alzheimer’s disease (AD) is the seventh cause of death in the world, and surprisingly one of the only ones without any effective treatment to cure or stop the disease. Several neuropathological studies have shown the correlation of neurofibrillary tangles (NFTs) burden with the degree of cognitive impairment in AD, whereas deposition of amyloid-β (Aß) plaques has failed to show this correlation. Despite continued emphasis on drug development targeting Aß plaques in various studies, the lack of a clear association between amyloids and cognitive impairments has resulted in limited positive outcomes. NFTs are the result of tau aggregation, a process in which the heparan sulphates have shown a crucial role. In vitro, the aggregation of tau is not possible in the absence of heparin, a highly sulphated heparan sulphate carrying a rare 3-O-sulphation. Here, we show that the gene expression of heparan sulphate 3-O-sulphotransferases, producing specific heparan sulphate chains, the 3-O-sulphated heparan sulphates, is under the control of TGF-ß signalling pathway. TGF-ß1 is a pleiotropic cytokine upregulated in AD patients and can modulate gene expression through its transcription factor SMAD4. Furthermore, we demonstrate that the neural heparan sulfate-glucosamine 3- sulphotransferase 2 (Hs3st2) is critical for the AD related tau abnormal phosphorylation and oligomerization, and that its loss of function decreases tau pathology, leading to the recovery of synapse density and connectivity, which is known to be correlated with an improvement in cognition and learning or memory. Together, our results position intracellular 3-O-sulphated heparan sulphates produced by Hs3st2 and its TGF-ß related regulatory pathway, as key modulators of AD tau pathology, opening a wide area of research with therapeutic potential for AD and other tauopathies.
Keywords: Heparan sulphates; TGF-ß1; TGF-ß signalling pathway; Tau; Alzheimer’s disease; HS3ST2; Tauopathie; ddc:500; ddc:600; ddc:610